Estudos de sinterização em cerâmicas de titanato de bário - Silva, Paola Vieira Alves (2016)
This work analyzes how different sintering temperatures affect the barium titanate obtained by solid-state reaction. BaTiO3 ceramics has been studied because of its properties, such as high dielectric constant, large pyroelectric coefficient and low manufacturing cost, compared to other lead-based ferroelectric materials. Among the technological applications of such materials, we can mentioned transducers, actuators, sensors, capacitors, permittivity thermistors and memory devices. The BaTiO3 was produced synthetically by solid-state reaction, where the powder was calcined at 950 °C, 1000 ° C, 1100 °C, 1150 °C and 1200 °C. In order to verify the materials purity we performed X-ray diffraction. The powders were then formed into discs of approximately 5 mm in diameter and 1 mm thickness and sintered at 1200°C, 1250 °C, 1300 °C and 1350 °C for 2 h. The density of the samples was obtained by the Archimedes method.